Brand Image, Product Quality and Promotion Influence Towards the Decision to Purchase Milo in Batam City - Ajeng Nur Aulia Putri; Yunisa Oktavia (Primanomics : Jurnal Ekonomi & Bisnis, 2024)
Chocolate-flavored milk drinks, including Milo, have become icons in the beverage industry with a long history that continues to grow. In Indonesia, the food and beverage industry, including dairy beverages, is experiencing rapid growth, but faces stiff competition. The purpose of this study is to describe the influence of brand image, product quality and promotion on the purchase decision of Milo products in Batam City. This study uses quantitative and descriptive, the population used is buyers or those who consume Milo products in Batam City, using the slovin formula with the results of the calculation of 100 respondents. In this study, the multiple linear regression analysis method was used with the help of SPSS 27. The results of the study can show that the brand image variable (X1) obtained a t-count value of 4.015 > t table of 1.984 and a significance of 0.000 < 0.05, a product quality variable (X2) obtained a t count of 2.252 > a t table of 1.984 and a significant < of 0.05, a promotional variable (X3) obtained a t count of 4.003 > a t table of 1.984 and a significance of 0.000 < 0.05. Brand image, product quality, and promotion have a significant influence Purchase decisions are aimed at the value of f hutung 46.641 > t table 2.70 and significant 0.000 < 0.05. The R2 value of 58.0% and the remaining 42.0% were influenced by other variables that were not mentioned in this study.